PENAPISAN TALASEMIA DENGAN PEMERIKSAAN KADAR HEMOGLOBIN - Subandrate Subandrate; Sadakata Sinulingga; Medina Athiah; Safyudin Safyudin; Fatmawati Fatmawati; Rini Yana (CV SWA Anugerah, 2024)
Thalassemia is a genetic disease that affects the hemoglobin component in red blood cells. Health education is expected to provide changes in people's knowledge and attitudes in recognizing and preventing thalassemia. In addition, thalassemia self-screening is a simple way to be able to recognize and prevent thalassemia independently and sustainably. This community service activity was carried out with the method of counseling and demonstration of thalassemia screening by checking hemoglobin levels. The activity was carried out in Sako Village, Palembang City on Sunday, October 23, 2022. The participants of the activity were the community and administrators of KJS Al Aqobah 2 Pusri, Sako, Palembang. Most of the participants were 61 years old for the counseling group, and 13 years old for the thalassemia screening group. The community was very enthusiastic about participating in this activity. Some of the important questions asked by participants were 1) Can thalassemia be transmitted? 2) Is thalassemia only inherited from the mother? 3) Can thalassemia be cured? Discussions about thalassemia are carried out in general in a series of events and individually between screening activities. The results of screening with hemoglobin examination showed that there were no participants who were indicated to have thalassemia. The hemoglobin levels of all participants were normal (above 12 g/dL). Tracing symptoms and family history showed that the participant's family had not been indicated as having thalassemia. The service activities have been carried out well and provide benefits for the participants. The community expects similar activities to be carried out simultaneously.